Abnormal Growth and Feeding Behavior in Upper Airway Obstruction in Rats - Tarasiuk, Ariel; Segev, Yael (Frontiers in Endocrinology, 2018)
Pediatric obstructive sleep apnea (OSA) is a syndrome manifesting with snoring and increased respiratory effort due to increased upper airway resistance. In addition to causing the abnormal sleep, this syndrome has been shown to elicit either growth retardation or metabolic syndrome and obesity. Treating OSA by adenotonsillectomy is usually associated with increased risk for obesity, despite near complete restoration of breathing and sleep. However, the underlying mechanism linking upper airways obstruction to persistent change in food intake, metabolism, and growth remains unclear. Rodent models have examined the impact of intermittent hypoxia on metabolism. However, an additional defining feature of OSA that is not related to intermittent hypoxia is enhanced respiratory loading leading to increased respiratory effort and abnormal sleep. The focus of this mini review is on recent evidence indicating the persistent abnormalities in endocrine regulation of feeding and growth that are not fully restored by the chronic upper airways obstruction (AO) removal in rats. Here, we highlight important aspects related to abnormal regulation of metabolism that are not related to intermittent hypoxia per se, in an animal model that mimics many of the clinical features of pediatric OSA. Our evidence from the AO model indicates that obstruction removal may not be sufficient to prevent the post-removal tendency for abnormal growth.